Corporate restructuring: film characteristics and performance - Fauzias Mat Nor; Norazlan Alias; Mohd Hasimi Yaacob (Penerbit Universiti Kebangsaan Malaysia, 2008)
Theoretically, corporate restructuring is meant to remove firms' operating and financial constraints and improve firm perfonnance. However, corporate restructuring announcement might be interpreted differently by the market. Using event-study method, this study examines the impact of corporate restructuring announcements made by selected firm on their stock prices. Overall, the effect of the restructuring announcements, made by these companies on stock prices was significant while the average two years of return on total assets and return on operating cash flow in the post restructuring period were mixed. Evidence also indicates that debt reduction, refocusing and alignment of interest between management and shareholders through board of directors' ownership do not constitute the main focus for some finns in the post restructuring period.